2022
DOI: 10.5398/tasj.2022.45.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Antibiogram of ESBL-Producing and Carbapenem-Resistant Escherichia coli from Rabbit, Swine, and Poultry in Malaysia

Abstract: The emergence of multidrug-resistance Enterobacteriaceae such as extended-spectrum β-lactamase (ESBL) producing Escherichia coli (E. coli) and carbapenem-resistant E. coli (CREC) has become an urgent veterinary and public health threat. These multidrug-resistant microorganisms are frequently associated with diseases that have high mortality with limited treatment options. This study aims to investigate the prevalence of ESBL producing E. coli and CREC from the rabbit, swine, and poultry and to determine the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Similarly, ESBL production from E. coli strains has been referred as a recent problem in poultry [50][51][52]. Although it is not very clear whether ESBL production from E. coli represents a major problem to the poultry sector, it might be a direct threat to public health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ESBL production from E. coli strains has been referred as a recent problem in poultry [50][51][52]. Although it is not very clear whether ESBL production from E. coli represents a major problem to the poultry sector, it might be a direct threat to public health.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ESBL-producing E. coli in poultry was 5.5%. These findings suggest that while ESBL-producing E. coli strains were present in poultry, they were not detected in rabbits or swine in this study [ 43 ]. The increasing detection of several ESBL-producing E. coli in fish farming has been reported to demonstrate resistance against those antibiotics in water and fish E. coli isolates and fish feed have been claimed to be a source of antimicrobial-resistant bacteria.…”
Section: Food-producing Animals As One Of the Potential Sources Of Fo...mentioning
confidence: 84%
“…Based on the analysis of three studies, it has been observed that there is a current trend of an increase in ESBL-producing E. coli strains in aquatic environments [44][45][46]. The prevalence rates may vary in different regions and can be influenced by various factors, such as management practices, antibiotic usage, and the dissemination of resistant bacteria in the environment [43]. ND-Not determined.…”
Section: Food-producing Animals As One Of the Potential Sources Of Fo...mentioning
confidence: 99%
“… 45 , 46 These results are contrary to those reported in a study conducted among livestock in Malaysia that indicated a very low prevalence of MDR ESBL-EC. 47 The difference in the MARI could be attributed to the variations in the regulation of antibiotic use in the two countries. This high degree of resistance in almost all the drug combinations in this study could be associated with epidemiological and practice factors.…”
Section: Discussionmentioning
confidence: 99%